2017
DOI: 10.1515/pterid-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Sleep onset insomnia, daytime sleepiness and sleep duration in relationship toToxoplasma gondiiIgG seropositivity and serointensity

Abstract: AbstractToxoplasma gondii (T. gondii) infects central nervous tissue and is kept in relative dormancy by a healthy immune system. Sleep disturbances have been found to precipitate mental illness, suicidal behavior and car accidents, which have been previously linked to T. gondii as well. We speculated that if sleep disruption, particularly insomnia, would mediate, at least partly, the link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…The questions “trouble staying asleep” (sleep maintenance), “problems during the day due to poor sleep” and “daytime sleepiness” were answered by 833 individuals, 455 (54.62%) of which were T. gondii seropositive. Other questions regarding sleep that did not include the ones mentioned above (because of a change in questionnaire length due to logistical issues), were previously analyzed in relationship to markers of chronic T. gondii infection [ 46 ]. Bedtime and wake-up time were self-reported and the mid-sleep time was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questions “trouble staying asleep” (sleep maintenance), “problems during the day due to poor sleep” and “daytime sleepiness” were answered by 833 individuals, 455 (54.62%) of which were T. gondii seropositive. Other questions regarding sleep that did not include the ones mentioned above (because of a change in questionnaire length due to logistical issues), were previously analyzed in relationship to markers of chronic T. gondii infection [ 46 ]. Bedtime and wake-up time were self-reported and the mid-sleep time was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…We thus reasoned that sleep impairment might mediate, at least in part, the link between T. gondii infection and psychiatric disorders and behavioral dysregulation. Recently, we reported in a sample of Old Order Amish, no associations of T. gondii IgG seropositivity and serointensity with bedtime difficulties or daytime sleepiness [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lancaster, PA receives an average annual rainfall of about 42.8 inches (108.7 cm) and an average annual snowfall of about 18.3 inches (46.5 cm). Lancaster County, PA was chosen for the study due to the high documented seroprevalence for T. gondii infection in the OOA community in the area [68] (Postolache et al, unpublished data), as compared to the general U.S. population [5]. Many cats freely roam in the Amish farms and feed by hunting rodents.…”
Section: Methodsmentioning
confidence: 99%
“…According to a series of cross-sectional studies conducted by the Centers for Disease Control and Prevention, the age-adjusted seroprevalence rate for T. gondii in the United States (U.S.)-born population, aged 12–49 years, continued to decline from nearly 14% (from 1988–1994) [3], to 9% (from 1999–2004) [4], to 6.7% (from 2009 to 2010) [5]. In comparison, Old Order Amish (OOA) from Lancaster County, Pennsylvania, a primarily agrarian community, have a much higher T. gondii seroprevalence rates (46–65%) [68](Postolache et al, unpublished data). T. gondii has three infectious stages, with all stages having the capability of infecting the definitive as well as the intermediate hosts, including tachyzoites, sporozoites (present in the oocysts), and bradyzoites (present in the tissue cysts) [1, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of Aβ in the brain is one of the first major pathological symptoms in AD and may be a trigger for sleep disorders; however, other factors, such as irregular physical activities or mealtimes of the elderly, exposure to insufficient daylight for institutional care, antidepressants, and medication for hypertension or heart diseases, may also play a role in the severity of sleep problems in patients with AD [ 219 ]. The results of two studies examining the relationship between T. gondii immunoglobulin G seropositivity and sleep problems have shown that sleep is unlikely associated with mental disorders [ 221 , 222 ]. However, T. gondii may directly affect sleep through dopamine endogenous production [ 148 , 223 , 224 ].…”
Section: Designmentioning
confidence: 99%